Simple Engineering of Polymer–Nanoparticle Hybrid Nanocapsules. Issue 8 (30th June 2016) - Sciortino, Flavien; Casterou, Gérald; Eliat, Pierre‐Antoine; Troadec, Marie‐Bérengère; Gaillard, Cédric; Chevance, Soizic; Kahn, Myrtil L; Gauffre, Fabienne
Abstract: A general method to generate hybrid hollow capsules is reported. The process is based on the stabilization of solvent droplets by nanoparticles, in macroscopically miscible mixtures of tetrahydrofuran (THF) and water. After addition of a crosslinking polymer and removal of the solvent core, capsules of diameter ca 100 nm are obtained. This novel strategy does not require the use of block copolymers. In contrast, most methods reporting the formation of hybrid nanocapsules incorporate nanoparticles into block‐copolymer polymersomes or use nanoparticles tethered with block‐copolymers. The nanocapsules were characterized using a full set of techniques including nanoparticle tracking analysis, electron microscopy and liquid phase atomic force microscopy. Our results show that the vesicular shape of the nanocapsules is templated by the liquid droplets. Nanocapsules were prepared from quantum dots, gold nanoparticles, superparamagnetic iron oxide nanoparticles and mixtures of particles. The entrapment of a fluorescent dye was also demonstrated. Thus, nanocapsules with dual properties (e.g., magnetic and fluorescent) are easily obtained. Interestingly, the magnetic nanocapsules enable magnetic resonance imaging contrast enhancement of tumors in vivo. Abstract : Hybridosomes : Although water and THF are known as miscible solvents, their mixtures contain droplets that template the self‐assembly of nanoparticles and polymers. This strategy was successfully applied to create hollow nanocapsules (∼100 nm) with a hybrid shell made of crosslinked polymers and nanoparticles. Magnetic nanocapsules proved to be efficient as in vivo MRI contrast agents for tumor imaging.